Accessing the Effect of Renewables on the Wholesale Power Market - Nure Alam, Mohammad (International Journal of Energy Economics and Policy, 2021)
The purpose of this paper is to examine how rising wind energy generation (in MWh) impact the wholesale power market’s volatility (in SEK) across four bidding regions in Sweden. Prior investigations show that though the increase in electricity production from wind energy lowers the average day-ahead electricity wholesale prices, however, uncertainty and volatility of market price could rise due to wind energy’s intermittent nature. This study results show that Swedish power market experiences higher price volatility in long-run frequency when the generation of wind electricity increases. The reason for this high and volatile electricity price might be found from inflexible baseload power generation. The paper further suggests that volatility in the Swedish power market could be increased due to ambitious renewable electricity target by the Swedish government. The analysis concludes by providing the evidence that further adjustment in regard to the energy and regulatory policies might foster the better integration of a higher share of renewables into the power system. Keywords: Renewable Electricity, Wind Energy, Electricity Market, Price Volatility, Regulatory Policies JEL Classification: Q470 DOI: https://doi.org/10.32479/ijeep.10756